The Analysis and Implementation of Psak 71 (Ifrs 9): Financial Instruments at PT X for The Year 2019 - Veren Hermawan; Indra Pratama (Conference Series, 2020)
PSAK 71 was issued by the Indonesian Accounting Standard Board (DSAK-IAI), as an adaptation of IFRS 9: Financial Instruments to replace the old accounting for financial instruments standard, PSAK 55 (IAS 39). The new accounting standard is implemented in Indonesia effective from January 2020. “PT X” is a private company in Indonesia that runs in the heavy equipment industry and was chosen to be the research subject. This research is conducted to identify the financial impacts arised from PSAK 71 (IFRS 9) implementation towards Statement of Financial Position, Income Statement and Statement of Cash Flow of PT X in 2019 compared to the previous accounting standard PSAK 55 (IAS 39). The result of this research shows that there is no significant impact towards PT X financial statements, specifically its Statement of Financial Position, Income Statement and Statement of Cash Flow.